2022
DOI: 10.1155/2022/5842677
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced ITGB4 Promotes Endothelial Cell Inflammation and Atherosclerosis

Abstract: The local heterogeneity in the distribution of atherosclerotic lesions is caused by local flow patterns. The integrin family plays crucial regulatory roles in diverse biological processes, but knowledge of integrin β4 (ITGB4) in shear stress-induced atherosclerosis is limited. This study clarified that low shear stress (LSS) regulates the generation of ITGB4 in endothelial cells with atheroprone phenotype to identify ITGB4’s role in atherosclerosis. We found that LSS led to an increase in ITGB4 protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The β4, α6β1, and β3 integrins that are present on ECs and VSMCs play roles in the inflammation and plaque formation of AS. Research has shown that β4 integrins on the plasma membrane of ECs activates a positive feedback signaling pathway by activating SRC and downstream NF-κB, the activation of which contributes to excessive transcriptional activity of β4 integrins; the activation of the pathway then upregulates the expression of endothelial inflammatory factors, leading to the development of AS (Figure 2) [38]. Furthermore, a similar mechanism has been reported in which the α6β1 integrins present on ECs bind to the EC-expressed matrix protein CCN1 to activate NF-κB, which forms a positive feedback loop with the CCN1 and α6β1 integrins and amplifies oxidative stress and inflammation in the arterial wall (Figure 2) [39].…”
Section: Integrins That Bind To Laminin Receptorsmentioning
confidence: 99%
“…The β4, α6β1, and β3 integrins that are present on ECs and VSMCs play roles in the inflammation and plaque formation of AS. Research has shown that β4 integrins on the plasma membrane of ECs activates a positive feedback signaling pathway by activating SRC and downstream NF-κB, the activation of which contributes to excessive transcriptional activity of β4 integrins; the activation of the pathway then upregulates the expression of endothelial inflammatory factors, leading to the development of AS (Figure 2) [38]. Furthermore, a similar mechanism has been reported in which the α6β1 integrins present on ECs bind to the EC-expressed matrix protein CCN1 to activate NF-κB, which forms a positive feedback loop with the CCN1 and α6β1 integrins and amplifies oxidative stress and inflammation in the arterial wall (Figure 2) [39].…”
Section: Integrins That Bind To Laminin Receptorsmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that ECs are critical sensors of shear stress that modulate endothelial structure, function, and permeability [ 59 ]. Low or low and oscillatory WSS triggers multiple pathways of intracellular signaling pathways that promote the expression of pro-proliferative and pro-inflammatory mechanosensitive genes while suppressing atheroprotective flow-dependent genes [ 60 ]. As a result, a flow-dependent inflammatory and infiltrative process is initiated with important implications for hemostasis and thrombosis, vascular tone, redox balance, vascular smooth cell proliferation and ultimately their osteoblastic transformation with subsequent plaque calcification [ 47 ].…”
Section: Is There a Reason For The Non-random Distribution Of Atheros...mentioning
confidence: 99%